Cancrum Oris (noma) in Children - Valadas, G (1998)
Cancrum oris, noma or gangrenous stomatitis is a disease which affects primarily undernourished and immunosuppressed young children. Frequent in underdeveloped countries, it also is seen in rare cases of patients with AIDS and leukemia in America and in Europe. Once fatal, the disease is now better understood and today the repair of its terrible sequels is looked upon as a great surgical challenge. This paper reports a case of noma in a 3-year-old black African female admitted to this Service. In an already advanced stage of this illness with severe sequelae, she presented with partial amputation of the lips (upper and lower), right cheek, right side of the nose and maxilla. The choice of treatment of the infected area and eventual reconstruction is discussed.